Upaya Meningkatkan Perkembangan Sosial Emosional Anak Usia Dini - Novi Mulyani (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2017)
Education in the family will build the character of a child, that surely will induce to the development in social environment. Thus, the emotional development must always be paid attention. One of the typical method in Islam version is qhashas or stories. Which is effective as the way to provide a metting the chatting with children. Preoccupation in substance delve into the story will produce what the Maslow called sympathetic that the most profound without realizing it. The stories will affect his personal development (social-emotional). Has established the attitudes of the moral values.